Analisis Perilaku Sosial Pengguna Moda Transportasi Perkotaan: Studi Kasus Mass Rapid Transit (MRT) DKI Jakarta - Pambudi, Andi Setyo; Sri Hidayati (Bappenas Working Papers, 2020)
After going through a long process, in March 2019, Jakarta resident have Mass Rapid Transit (MRT) as a modern mass transportation mode. The presence of the MRT planned since 1986 is expected to be one of the solution to dealing with the heavy traffic in Jakarta that seemed impossible to handle. The problems that followed is MRT passenger behaviour is not prepared with all the regulations that must be enacted in the use of MRT, so that various violations of the regulations are found. This paper attempts to find factors that cause regulatory violations and factor that lead to changes in passenger behaviour in addressing MRT presences based on literature, big data, and qualitative descriptive analysis. It is also expected to be able to provide recommendations that can be given with an emphasis on social aspects. Studies are conducted using secondary data on passenger behaviour in MRT and the facility obtained from various sources and observations. Studies describe social phenomena occurring in communities where MRT trials are caused by culture and people’s readiness to use new technologies, and the existence of the MRT since one year of operation is able to change people's behavior.